Management of MEC Service and Optimization of Mission Migration in LEO Satellite Networks - Zhihui LIU; Huan WEI; Jie YIN; Junyi WANG; Shichao JIN; Tao DONG (天地一体化信息网络)
Low earth orbit (LEO) satellites play an important role in the communication of earth observation and wide area coverage because of their advantages of short transmission delay and low deployment cost.Due to limited size and weight of LEO satellite platform, the function of each LEO satellite node is relatively single, which requires effi cient collaboration among various LEO satellite nodes to form a high-performance satellite network with decentralized functions and converged capabilities.It puts forward certain requirements for network service management.Aiming at the cooperative scenario that remote sensing satellites migrate observated task data to LEO satellite constellation with mobile edge computing (MEC) service deployed, the MEC service management model based on software defi ned network in LEO satellite networks was studied, a cross-slot task migration optimization method with the aid of time extended graph was proposed.The simulation results showed that the task migration optimization method could eff ectively reduced the cost of observation satellite processing tasks.And it could off ered the management model for LEO satellite networks that deployed MEC servers.